How do you solve the following system using elimination!
2x-3y=61
2x+y=-7
$\displaystyle 2x-3y=61$
$\displaystyle 2x+y=-7$
subtract the 2nd equation from the 1st equation.
$\displaystyle {2x-3y=61}$
$\displaystyle \frac{-2x-y=7}{-4y=68}$
$\displaystyle y=-17$
then substitute
$\displaystyle 2x-3(-17)=61$
$\displaystyle 2x+51=61$
$\displaystyle 2x=10$
$\displaystyle x=5$
then check:
$\displaystyle 2x-3y=61$
$\displaystyle 2(5) - 3(-17) = 61$
$\displaystyle 61= 61$
$\displaystyle 2x+y=-7$
$\displaystyle 2(5) + (-17) = -7$
$\displaystyle -7=-7$